Anti-allergic ophthalmic drugs in general practice: Which, why and when? - N. Mohamed; D.P. Smit (South African Family Practice)
Ocular allergies present in many different guises. They may vary from self-limiting episodes of acute allergic conjunctivitis, to potentially sight-threatening chronic conditions, such as vernal keratoconjunctivitis. This article provides a brief description of the different ocular allergic conditions to aid accurate diagnosis. It also focuses on the different types of anti-allergic ophthalmic preparations and how to employ them in a logical, stepwise management strategy to obtain optimal results, while minimising exposure to potent drugs with potentially serious side-effects.